Nanocomposites based on laponite and carboxymethyl cellulose/hyaluronic acid for organic light-emitting diodes substrates - Bortoletto-Santos, Ricardo [UNESP]; Onishi, Bruno Seiki Domingos [UNESP]; de Farias, Renan Lira [UNESP]; Santagneli, Sílvia Helena [UNESP]; Ribeiro, Sidney José Lima [UNESP] (My University, 2022)
Laponite can improve mechanical strength and preserve the flexibility of sustainable polymers films desirable for application as a Flexible Organic Light-Emitting Diodes substrate. The nanocomposites were based on laponite and carboxymethyl cellulose/hyaluronic acid. The nanocomposites showed adequate flexibility, as well as the laponite showed good dispersion in the polymeric matrix, making them a good candidate for final application as a substrate for FOLED devices.